The history of Cuxham (Co. Oxon.) - Harvey, P (1960)
﻿ Cuxham is a small parish, less than a square mile in extent, lying twelve miles south-east of Oxford. Historically, it is a perfect example of the classical midland manor, in which vill, parish and manor coincide, forming a single economic and social unit. Since 1271 it has belonged to Merton College, which possesses an abundance of records of Cuxham; although later material has also been used, the present study is concerned mainly with the period before 1400, for which the surviving evidence (especially the account rolls and court rolls) is outstanding. Since it is intended as a contribution to general hist«ric«,l knowledge, most attention is paid to problems which seem to be of general relevance, like.ly to apply to other places besides Cuxham. A great deal of the evidence is embodied in the tables, maps and diagrams grouped together at the end, and much of the thesis takes the form of a commentary on these Illustrations. Only a few documents are reproduced, but full illustrative extracts are given in the footnotes. The introductory chapter opens with an account of the parish's early history; it is shown that its woodland was cleared first from the valley, then from the higher ground, and that by 1086 nearly all the land had been converted to arable. There follow an account of the ownership of the manor before it passed to Merton College, and a detailed discussion of the sources for its history. The next ciiapter is a general account of the parish's topography and place-names. The village arable was regularly tilled on the three-field system until 1846; starting from a survey of 1767, it is possible to reconstruct partial maps of the fields in the seventeenth and fifteenth centuries, although the names of many furlongs changed from one generation to another. The demesne arable did not lie in scattered strips like the tenants 1 lands, but in compact blocks formed probably in the early thirteenth c;entury. The plan of the village has changed little since the middle ages; the manor farm, the rectory and the two mills all occupied the same sites then as now. There is a short discussion of the names given to the tenements in the fourteenth and fifteenth centuries, of which some survive as the names of closes. Turning then to medieval Cuxham, the chapter on the manorial demesne, 1271-1359, opens with an examination of the curia, its buildings and their construction and use. This is followed by an account of the demesne arable. It is shown that for most of this period its area remained static, and that the apparent changes shown on the account rolls occur because areas are there given sometimes in statute, sometimes in customary acres. After the Black Death, however, parcels of the demesne were let out to the tenants, at first for short terms, but lateff on; a permanent basis. Wheat was the demesne's principal cash crop, while the springcorn field was sown mainly with oats, barley and dredge. The proportion of each type of corn sown, the uses to which each was put, the times of sowing and the annual yields - which were extremely high - are all discussed; this involves an examination of the various 'increments 1 of corn, for which the bailiffs had to answer after the Black Death, and in particular of the system of heaping every eighth bushel, which is described by Walter of Henley, and which is shown to have originated in the agreements made with the hired threshers. A brief survey of the livestock and equipment is followed by an account of the management of the demesne. From 1288 to 1349 this was in the hands of only two successive reeves; they are shown to have been men of substance, occupying a post of trust and responsibility. The account rolls' evidence of their mounting debts to the College is shown to belie their actual financial position, for these sums were balanced by money due to them from other sources. Cuxham also provides a good deal of evidence of the sort of perquisite that the office brought to the reeves. From 1349 to 1359 there were no fewer than seven bailiffs or reeves at Cuxham; conditions after the Black Death clearly made it difficult for the College to find satisfactory managers, and this may have been the cause of the manor's being leased to farmers from 1359 onwards. The chapter concludes with an account of the demesne labour force: the famuli, the occasional hired labourers and the customary tenants' labour services. It is shown that even before 1349, when heavy labour services were being exacted in full, they provided only about one-third of all the work done on thte demesne; most of the rest was done by the famuli. After the Black Death, labour services virtually ceased, and the number of famuli gradually fell, while amounts spent on outside hired labour rose proportionately. The next chapter deals with the manor's outside contacts from 1271 to 1359, and gives first an account of its position in the Merton College estates. Its contacts with the College's other manors were frequent but irregular; although the manor was closely supervised by the Warden and Fellows, it was administered as a single independent unit. The College's records of the manor's profits are discussed, also the deliveries of produce from Cuxham to the College, which were sometimes entered on the accounts as sales. But Cuxham's position in its region was probably more important to its economy than its links with other Merton manors. It had rights of intercommoning with at least one neighbouring parish, while thetdemesne was dependent on local sources outside Cuxham for all of its timber and brushwood, and for some of its hay. Abingdon, not the more accessible Wallingford, was the manor's principal source of supply for livestock and other items, while Henley-ott* Thames was its principal market for corn, which was presumably sent down the river to London. Two aspects of the manor's contacts with the royal ddministration are eiiamined in detail: the assessment of the demesne for taxation, with the use of bribery and its success; and royal exactions in the shape of the requisition of the demesne's cart and the enforced sale of corn, from which Cuxham suffered most in the 1340's, and which gave the reeve much trouble in securing payments. The next chapter is concerned with the tenants and other inhabitants of Cuxham from 1240 to 1400. Prom about 1290 there was anly a single free tenant; an account is given of this family's history and of its properties, scattered in at least seven parished besides Cuxham. The obligations of the unfree tenants - villeins and cottagers — are examined, and it is shown that the second half o£ the thirteenth century s§w the position of the lord of the manor in Cuxham considerably strengthened, A reconstruction of the locations of the tenants* holdings points to the villein tenements having an older origin than the cottages; and the distinction between the two classes of peasant is borne out by differences in the customs of succession and in economic status, which are both described in detail. It is interesting to note that the tenants 1 livestock and crops differed considerably from those of the demesne; horses were used instead of oxen, rye was grown as well as wheat, and vetch, not oats, was the principal fodder crop. The peasants' use of surnames is examined; it is shown, inter alia, that a man marrying a tenant's widow would take the surname of her first husband. Before 1349 many of the peasants were employers of labour, but there is no sign of this after the Black Death, which many changes at Cuxham besides great immediate mortality. One or two tenements were never re-occupied; the rest were filled by 1355, but were held at far lower real rents than before. Even so, it is syggested tha# the Black Death probably resulted in a lowering of the economic and social status of the peasants at Cuxhannp The chapter concludes with an account of the village's other inhabitants, paying particular attention to the management of the two corn mills (of which one was probably still a hand-mill until after 1300) and the fulling mill. The thesis closes with a short account of the church, the rectors and the glebe, for which very little medieval evidence survives. No general conclusion can be put forward; any value the Cuxham material may possess lies in the light it throws on many small but important details of English rural life in the fourteenth century.